Protein palmitoylation: Palmitoyltransferases and their specificity. Issue 11 (June 2017) - Tabaczar, Sabina; Czogalla, Aleksander; Podkalicka, Joanna; Biernatowska, Agnieszka; Sikorski, Aleksander F
A plethora of novel information has emerged over the past decade regarding protein lipidation. The reversible attachment of palmitic acid to cysteine residues, termed S -palmitoylation, has focused a special attention. This is mainly due to the unique role of this modification in the regulation of protein trafficking and function. A large family of protein acyltransferases (PATs) containing a conserved aspartate–histidine–histidine–cysteine motif use ping-pong kinetic mechanism to catalyze S -palmitoylation of a substrate protein. Here, we discuss the topology of PAT proteins and their cellular localization. We will also give an overview of the mechanism of protein palmitoylation and how it is regulated. New information concerning the recent discovery of depalmitoylating enzymes belonging to the family of α/β-hydrolase domain-containing protein 17 (ABHD17A) is included. Considering the recent advances that have occurred in understanding the mechanisms underlying the interplay between palmitoylation and depalmitoylation, it is clear that we are beginning to understand the fundamental nature of how cellular signal-transduction mediates membrane-level organization in health and disease. Impact statement: Protein palmitoylation is one of most important reversible post-translational modifications of protein function in cell-signaling systems. This review gathers the latest information on the molecular mechanism of protein palmitoyl transferase action. It also discusses the issue of substrate specificity of palmitoyl transferases. Another important question is the role of depalmitoylation enzymes. This review should help to formulate questions concerning the regulation of activity of particular PATs as well as of depalmitoylating enzymes (APT).